2009
DOI: 10.1111/j.1469-8137.2008.02754.x
|View full text |Cite
|
Sign up to set email alerts
|

Coppicing shifts CO2 stimulation of poplar productivity to above‐ground pools: a synthesis of leaf to stand level results from the POP/EUROFACE experiment

Abstract: SummaryA poplar short rotation coppice (SRC) grown for the production of bioenergy can combine carbon (C) storage with fossil fuel substitution. Here, we summarize the responses of a poplar (Populus) plantation to 6 yr of free air CO 2 enrichment (POP/ EUROFACE consisting of two rotation cycles). We show that a poplar plantation growing in nonlimiting light, nutrient and water conditions will significantly increase its productivity in elevated CO 2 concentrations ([CO 2 ]). Increased biomass yield resulted fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 113 publications
3
47
0
Order By: Relevance
“…To date, existing experiments have demonstrated that rising atmospheric [CO 2 ] results in increases in net primary production (NPP) and C storage in forest vegetation, e.g. (Calfapietra et al, 2003;DeLucia et al, 1999;Gielen et al, 2005;Hamilton et al, 2002;Handa et al, 2006;Karnosky et al, 2003;Liberloo et al, 2009;Norby et al, 2002). Norby et al (2005) analyzed the response of NPP (g C m −2 y −1 ) to elevated [CO 2 ] in four forest FACE experiments and calculated the following regression NPP elev = 1.18×NPP amb + 55.4 (r 2 = 0.97).…”
Section: Introductionmentioning
confidence: 99%
“…To date, existing experiments have demonstrated that rising atmospheric [CO 2 ] results in increases in net primary production (NPP) and C storage in forest vegetation, e.g. (Calfapietra et al, 2003;DeLucia et al, 1999;Gielen et al, 2005;Hamilton et al, 2002;Handa et al, 2006;Karnosky et al, 2003;Liberloo et al, 2009;Norby et al, 2002). Norby et al (2005) analyzed the response of NPP (g C m −2 y −1 ) to elevated [CO 2 ] in four forest FACE experiments and calculated the following regression NPP elev = 1.18×NPP amb + 55.4 (r 2 = 0.97).…”
Section: Introductionmentioning
confidence: 99%
“…Carbon enrichment was achieved by injecting pure CO 2 through laser-drilled holes in tubing mounted on six masts placed in an octagonal pattern with a diameter of about 22 m (Miglietta et al 2001). The elevated CO 2 concentrations, measured at 1-min intervals, were within 20 % deviation from the pre-set target concentration of 550 ppm for 91 % of the time (1999)(2000)(2001)(2002)(2003)(2004) (Liberloo et al 2009). The trees were coppiced after the first three growing seasons (1999)(2000)(2001).…”
Section: Methodsmentioning
confidence: 71%
“…At the EuroFACE experiment, total plant C had increased by 21 % after 6 years of elevated CO 2 treatment (Liberloo et al 2009). Above ground litter accumulated in forest floor litter layers (L ?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with seedlings, sprouts are characterized by a faster above-ground growth during early development (Herve & Ceulemans 1996, Liberloo et al 2009, Drake et al 2012, although this does not entails a higher photosynthetic ability of sprouts. Indeed, seedlings allocate more assimilated carbon to below-ground biomass and root development than plants from coppicing (Drake et al 2009).…”
Section: Discussionmentioning
confidence: 99%